2019
DOI: 10.1002/pbc.28010
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment with daratumumab for post‐HSCT refractory hemolytic anemia

Abstract: Autoimmune cytopenias (AIC) following allogeneic hematopoietic stem cell transplantation (HSCT) may cause significant morbidity and mortality and are often challenging to treat. We present a case of a pediatric patient with primary myelofibrosis of infancy caused by VPS45 protein deficiency, who developed severe refractory hemolytic anemia and immune‐mediated thrombocytopenia 3.5 months following HSCT. After the failure of several treatments, he received daratumumab, an anti‐CD38 specific antibody, and demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…This is consistent with a previous case report where daratumumab achieved a sustained remission in an infant with both AIHA and ITP who had previously failed multiple lines of therapy. 33,[38][39][40][41][42] Although reports agree that there is efficient periph-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with a previous case report where daratumumab achieved a sustained remission in an infant with both AIHA and ITP who had previously failed multiple lines of therapy. 33,[38][39][40][41][42] Although reports agree that there is efficient periph-…”
Section: Discussionmentioning
confidence: 99%
“…3,4 AICs tend to have a protracted course and can be resistant to multiple therapies. 5,6 Prior studies have identified several risk factors for AIC development including nonmalignant transplant indications, chemotherapy naivety, unrelated donors, cord blood stem cell source, graft-vs-host disease (GVHD), reduced-intensity preparative regimens, serotherapy, and cytomegalovirus (CMV) reactivation. [7][8][9][10] Corticosteroids and rituximab are the most common first-line therapies for AICs.…”
mentioning
confidence: 99%
“…In a retrospective study, bortezomib (the first registered proteasome inhibitor) together with other drugs elicited a positive response in patients with refractory wAIHA [111,112]. Daratumumab (anti CD38 monoclonal antibody) has shown a rapid and sustained response in the treatment of refractory AIHA after HSCT in children [113] and in adults [114]. Proliferation disorder and apoptosis of pathological B lymphocytes is obtained by means of bruton tyrosine kinase (BTKs) inhibitors and antibodies directed against CD20 or CD52.…”
Section: Future Prospects Of Aiha Therapymentioning
confidence: 99%
“…The activity of DARA has been noted in the treatment of post-transplant autoimmune hemolytic anemia, mostly in pediatric patients [ 65 , 66 , 67 ]. In such setting, DARA showed encouraging results also as a rescue therapy in pre-treated patients refractory to common drugs such as rituximab, alemtuzumab, bortezomib, mycophenolate mofetil (MMF), sirolimus, and ibrutinib [ 68 ].…”
Section: Clinical Applications Outside MMmentioning
confidence: 99%